Smart gloves with strain/pressure dual-mode tactile sensor for UAV flight control - Zikai Yang; Qihao Zhang; Qin Luo; Jianhao Shen; Can Yang; Dai Li; Xiaohong Yin; Xiaohua Liu (Materials & Design)
Unmanned aerial vehicle (UAV) flight control enables precise navigation and obstacle avoidance in harsh weather conditions or challenging terrains, whereas conventional control methods mainly rely on external devices with operation complexity, limited flexibility and slower response time. This paper develops a sensing glove integrated with ultra-sensitive dual-mode e-skin for finger compression-based UAV flight control, where any of the pressure, strain, or their combinations can correspond to diverse signals in real time without signal overlap. The proposed polyurethane (TPU)/multi-walled carbon nanotube (MWCNT) electronic skin, termed TMES, features a flexible, biomimetic polydimethylsiloxane (PDMS) microcones interlocked with a microscale cracked TPU/MWCNT conductive network, exhibiting exceptional sensitivity in its positive resistance response to strain (630 at 70 %) and negative resistance response to pressure (−0.14004 kPa−1 in the 0–2.5 kPa range), as well as long-term stable working performance (>10,000 cycles). Extensive tests have confirmed that TMES is capable of accurately distinguishing a series of precise physiological signals and joint movements such as pulse, heartbeat, breathing and maintain reliable performance among multiple activities including bending, stretching, and pressing. The wireless sensing glove equipped with TMES has been implemented successfully for practical missions on real-world semi-physical simulation platform scenarios comprising disaster rescue and high-rise delivery.